Placental ESRRG-CYP19A1 Expressions and Circulating 17-Beta Estradiol in IUGR Pregnancies - Anelli, Gaia Maria; Mandò, Chiara; Letizia, Teresa; Mazzocco, Martina Ilaria; Novielli, Chiara; Lisso, Fabrizia; Personeni, Carlo; Vago, Tarcisio; Cetin, Irene (Frontiers in Pediatrics, 2019)
Introduction: Sex steroids are regulating factors for intrauterine growth. 17-β Estradiol (E2) is particularly critical to a physiological pregnancy, as increased maternal E2 was correlated to lower birth weight. The placenta itself is a primary source of estrogens, synthetized from cholesterol precursors. Cytochrome P450 aromatase (encoded by CYP19 gene) is a rate-limiting enzyme for E2 biosynthesis. CYP19 transcription is supported by Estrogen Related-Receptor Gamma (ERRγ), thus having an indirect role in placental steroidogenesis. Here we investigated maternal E2 levels and placental CYP19 and ERR expressions in pregnancies with intrauterine growth restriction (IUGR). Methods: Singleton pregnancies were studied. E2 was measured in maternal plasma by electrochemiluminescence in 16 term controls and 11 IUGR (classified by umbilical artery doppler Pulsatility Index) at elective cesarean section, and also in 13 controls during pregnancy at a gestational age comparable to IUGR. CYP19 and ERRγ expressions were analyzed in placental tissue. Maternal/fetal characteristics, placental and molecular data were compared among study groups and tested for correlations. Results: Maternal E2 plasma concentrations were significantly decreased in IUGR compared to controls at delivery. When analyzing normal pregnancies at the same IUGR gestational age, E2 levels were not different to IUGR. However, E2 levels at delivery positively correlated with placental efficiency. Placental CYP19 was significantly higher in IUGR placental tissue versus controls, with levels specifically increased in female IUGR placentas. ERRγ expression was not different among groups. Discussion: We report a positive correlation between 17-β Estradiol levels and placental efficiency, that might indicate a disrupted steroidogenesis in IUGR pregnancies. Moreover, we showed alterations of CYP19 in IUGR placentas, possibly indicating a compensatory effect to the adverse IUGR intrauterine environment, also depending on fetal sex. Further studies are needed to deeper investigate IUGR alterations in the complex interaction among molecules involved in placental steroidogenesis.